Ongoing HIV transmission following a large outbreak among people who inject drugs in Athens, Greece (2014–20). (21st February 2022) - Roussos, Sotirios; Paraskevis, Dimitrios; Psichogiou, Mina; Kostaki, Evangelia Georgia; Flountzi, Eleni; Angelopoulos, Theodoros; Chaikalis, Savvas; Papadopoulou, Martha; Pavlopoulou, Ioanna D.; Malliori, Meni; Hatzitheodorou, Eleni; Pylli, Magdalini; et al.
Abstract: Background and Aims: The human immunodeficiency virus (HIV) outbreak among people who inject drugs (PWID) in Athens, Greece in 2011–13 was the largest recent epidemic in Europe and North America. We aimed to assess trends in HIV prevalence, drug use and access to prevention among PWID in Athens to estimate HIV incidence and identify risk factors and to explore HIV‐1 dispersal using molecular methods during 2014–20. Methods: Two community‐based HIV/hepatitis C programmes on PWID were implemented in 2012–13 ( n  = 3320) and 2018–20 ( n  = 1635) through consecutive respondent‐driven sampling (RDS) rounds. PWID were uniquely identified among rounds/programmes. We obtained RDS‐weighted HIV prevalence estimates per round for 2018–20 and compared them to 2012–13. We assessed changes in HIV status, behaviours and access to prevention in PWID participating in both periods. We estimated HIV incidence in a cohort of seronegative PWID as the number of HIV seroconversions/100 person‐years during 2014–20 and used Cox regression to identify associated risk factors. Molecular sequencing and phylogenetic analysis were performed in HIV seroconverters. Results: HIV prevalence per round ranged between 12.0 and 16.2% in 2012–13 and 10.7 and 11.3% in 2018–20 with overlapping 95% confidence intervals (95% CI). Among PWID participating in both programmes, HIV prevalence (95% CI) increased from 14.2% (11.7–17.1%) in 2012–13 to 22.0% (19.0–25.3%) in 2018–20 ( P  < 0.001). There was a deterioration in socio‐economic characteristics such as homelessness [from 16.2% (95% CI = 13.5–19.2%) to 25.6% (22.3–29.0%)], a shift in cocaine use [16.6% (13.9–19.6%) versus 28.1% (24.7–31.7%], reduced access to free syringes [51.8% (48.0–55.7%) versus 44.5% (40.7–48.3%)] and a decrease in daily injecting [36.2% (32.6–39.9%) versus 28.5% (25.2–32.1%)]. HIV incidence (95% CI) in 2014–20 was 1.94 (1.50–2.52) new cases/100 person‐years and younger age, lower educational level, larger injection network and daily injecting were risk factors. Almost 9% of HIV seroconversions occurred within a newly expanding phylogenetic cluster. Conclusions: In Athens, Greece, compared with the period 2012–13, in the period 2018–20 there was a deterioration in socio‐economic conditions among people who inject drugs, an increase in the use of cocaine, reduced access to needle and syringe programmes and stable low levels of human immunodeficiency virus testing. Ongoing human immunodeficiency virus transmission was documented during 2014–20 in existing as well as new transmission clusters.